Advancing Quality Risk Management: A Comparative Overview of Traditional and Modern Tools in Pharma - Samanta, Sayan; Brahma, Pratyush Kumar; Rathi, Sanjesh (Journal of Neonatal Surgery, 2025)
A key component of pharmaceutical manufacturing, quality risk management (QRM) guarantees patient safety, product quality, and regulatory compliance throughout the product lifecycle. ICH Q9 and its Q9(R1) version refined risk assessment formality, decision-making, and product availability concerns. The conventional tool includes hazard analysis, FMEA, HACCP, and fault-tree analysis; innovative uses of real-time release testing, statistical process control, and risk-based oversight showed added value. Real-time monitoring and adaptable, flexible decision-making to reduce errors are made possible by technologies like PAT and continuous manufacturing. Although there are still challenges with understanding and governance, the potential given by digitalization, AI, ML, and predictive analytics enhance early deviation discovery and probabilistic evaluation. Newer technologies like digital twins and blockchain offer scenario testing, supply-chain resiliency, and traceability.Although there are still challenges with understanding and governance, the potential given by digitalization, AI, ML, and predictive analytics enhance early deviation discovery and probabilistic evaluation. Newer technologies like digital twins and blockchain offer scenario testing, supply-chain resiliency, and traceability.Still the limitations in ML understanding , regulatory harmonization, scalable digital twin adoption, and cross-industry benchmarking persists. The present status, developments, and prospects of QRM across global pharmaceutical production are highlighted in this article